Intelligent Fire Detection and Alarm System - Samamrah, Asala; Najajrah, Haleema; Fanoun, Haleema (جامعة بوليتكنك فلسطين - اتصالات, 2019)
أنظمة التيار المنخفض هي كافة أنظمة الهندسة الكهربائية التي تستخدم تقنية اشارة التيار الكهربائي المنخفض . لتطور التكنولوجيا في حياتنا المعاصرة في فلسطين بدأت التطبيقات الخاصة بهذه األنظمة بالتزايد نظرا . بعض أنظمة التيار ً المنخفض تختص بالسالمة مثل نظام الكشف واتانذار عن الحريق ونظام هاتف الحريق ونظام اتاخالء العام. وبعضها تختص بالحماية مثل نظام كاميرات المراقبة ونظام التحكم في بوابات الدخول والخروج . وبعض األنظمة مختصة بإرسال االشارة الصوتية مثل نظام النداء العام ونظام اتاجتماع الاوتي . والبعض االخر مختص بتوظيف التكنولوجيا في توفير الرفاهية للمستخدمين مثل نظام جودة الاوت وكفاءته ونظام العرض الاوتي والمرئي ونظام الساعات المركزية ونظام التلفزيون المركزي . في مشروعنا سنقدم كتابا نظريا يحتوي على كافة أنظمة التيار الخفيف وأيضا يحتوي على تطبيق عملي ألحد هذه األنظمة وهو نظام انذار الحريق لكي يعتمد كمساق نظري وعملي لطالب الهندسة الكهربائية والحاسوب في جامعة بوليتكنك فلسطين . Low current systems are Electrical Engineering systems that operate and function using low current signal. The applications of low current systems are increasing in Palestine due to development in technology. Some of these systems specialize in a human safety such as Fire Alarm System, Fire Telephone System and Voice Evacuation System. Some of these systems specialize in security such as CCTV System and Access Door Control System. Some of these systems specialize in voice transferring such as Public Address System and Audio Conference System. Some of these systems specialize to employ the technology in the human luxury such as Professional Audio System, AV System, MATV/IPTV System and Master Clock System. In this project, will provide a theoretical book containing all low current systems. We will present a practical DEMO for Fire Alarm Systems to be as one of the elective courses for Electrical and Computer Engineering students.
CD, no of pages 107,اتصالات 2/2019